Impact of cultivation conditions on physicochemical characteristics of Miscanthus × giganteus biomass - R. A. Newton; V. Pidlisnyuk; R. Pohl; A. Mamirova; T. Zschunke (International Journal of Environmental Science and Technology, 2025)
Miscanthus × giganteus has emerged as a successful energy crop for remediating marginal land, offering potential as an alternative energy source for climate change mitigation. This study aimed to assess the physicochemical properties for gasification of Miscanthus × giganteus biomass from plantations with diverse soil origins, characteristics, contamination levels, age, and climate conditions, aiming to determine their influence on the energy properties. Fuel parameters, i.e.: ash content, volatile matter, calorific value, ultimate analysis, and ash melting behavior were measured. Analysis of biomass samples revealed significant variations in the ash content and volatile matter with the average values of 4.5 and 78.8%, respectively, depending of the produced biomass. The calorific value remained consistently high, ranging from 18 to 19 MJ kg −1 , even when biomass was derived from the contaminated soil. Additionally, biomass ash exhibited complete melting at temperatures exceeding 1300 °C, signifying its suitability for gasification without encountering technical obstacles. Employing PCA analysis, the significance of plantation age, location, and soil characteristics in shaping the physicochemical properties of Miscanthus × giganteus biomass for gasification was highlighted. The results illustrated that soil contamination by trace elements had a minimal impact on the physicochemical properties, whereas plantation age and climate conditions significantly influenced to the fuel properties of biomass.

Plastic as a Sediment – A universal and objective practical solution to growing ambiguity in plastic litter classification schemes - C.E. Russell; F. Pohl; R. Fernández (Earth-Science Reviews, 2025)

Phenology Across Scales: An Intercontinental Analysis of Leaf‐Out Dates in Temperate Deciduous Tree Communities - Nicolas Delpierre; Suzon Garnier; Hugo Treuil‐Dussouet; Koen Hufkens; Jianhong Lin; Colin Beier; Michael Bell; Daniel Berveiller; Matthias Cuntz; Giulio Curioni; Kyla Dahlin; Sander O. Denham; et al. (Global Ecology and Biogeography, 2024)
Aim To quantify the intra‐community variability of leaf‐out (ICVLo) among dominant trees in temperate deciduous forests, assess its links with specific and phylogenetic diversity, identify its environmental drivers and deduce its ecological consequences with regard to radiation received and exposure to late frost. Location Eastern North America (ENA) and Europe (EUR). Time Period 2009–2022. Major Taxa Studied Temperate deciduous forest trees. Methods We developed an approach to quantify ICVLo through the analysis of RGB images taken from phenological cameras. We related ICVLo to species richness, phylogenetic diversity and environmental conditions. We quantified the intra‐community variability of the amount of radiation received and of exposure to late frost. Results Leaf‐out occurred over a longer time interval in ENA than in EUR. The sensitivity of leaf‐out to temperature was identical in both regions (−3.4 days per °C). The distributions of ICVLo were similar in EUR and ENA forests, despite the latter being more species‐rich and phylogenetically diverse. In both regions, cooler conditions and an earlier occurrence of leaf‐out resulted in higher ICVLo. ICVLo resulted in ca. 8% difference of radiation received from leaf‐out to September among individual trees. Forest communities in ENA had shorter safety margins as regards the exposure to late frosts, and were actually more frequently exposed to late frosts. Main Conclusions We conducted the first intercontinental analysis of the variability of leaf‐out at the scale of tree communities. North American and European forests showed similar ICVLo, in spite of their differences in terms of species richness and phylogenetic diversity, highlighting the relevance of environmental controls on ICVLo. We quantified two ecological implications of ICVLo (difference in terms of radiation received and exposure to late frost), which should be explored in the context of ongoing climate change, which affects trees differently according to their phenological niche.

The dynamic ocean redox evolution during the late Cambrian SPICE: Evidence from the I/Ca proxy - Ruliang He; Alexandre Pohl; Ashley Prow; Ganqing Jiang; Chin Chai Huan; Matthew R. Saltzman; Zunli Lu (Global and Planetary Change, 2024)

Conserved worker policing in African carpenter ants with drastically different egg chemotypes - Jan Buellesbach; Janina Rinke; Leonie Reuter; Jurian M. Thomas; Vivien Hartmann; Marius Pohl; Jürgen Gadau; Ulrich R. Ernst (Evolutionary Ecology, 2023)
Distinctive chemical signatures have the potential to serve as discriminatory cues for olfactory recognition mechanisms. Cuticular hydrocarbon (CHC) profiles are among the most prominent chemical signatures in insects that can be highly diverse even among closely related species and between populations with similar ecology. Particularly within the major insect order Hymenoptera, CHC profiles are characterized by high complexity and variation with the potential to evolve rapidly. In this study, we found two very distinct CHC chemotypes distinguishing sympatric colonies of the African carpenter ant Camponotus maculatus (Hymenoptera: Formicinae). These chemotypic differences were mainly detected on the surface profiles of eggs produced by either queens or isolated worker groups. In one chemotype, queen- and worker-laid eggs are very similar. This is largely contrasted by the other chemotype, where queen-laid eggs clearly differ from worker-laid eggs with several prominent queen-exclusive compounds. However, workers display a stable behavior of discriminating against and selectively disposing of worker-laid eggs i.e., worker policing, independent of egg chemotype. Furthermore, genetic barcoding of workers revealed a clear separation between colonies characterized by producing these two distinct egg chemotypes, which may indicate that these colonies belong to a cryptic species complex. Interestingly, worker policing behaviour appears to be evolutionarily conserved, despite the strikingly different egg surface profiles.

Vulnerability to climate change of managed stocks in the California Current large marine ecosystem - Michelle M. McClure; Melissa A. Haltuch; Ellen Willis-Norton; David D. Huff; Elliott L. Hazen; Lisa G. Crozier; Michael G. Jacox; Mark W. Nelson; Kelly S. Andrews; Lewis A.K. Barnett; Aaron M. Berger; Sabrina Beyer; et al. (Frontiers in Marine Science, 2023)
Introduction Understanding how abundance, productivity and distribution of individual species may respond to climate change is a critical first step towards anticipating alterations in marine ecosystem structure and function, as well as developing strategies to adapt to the full range of potential changes. Methods This study applies the NOAA (National Oceanic and Atmospheric Administration) Fisheries Climate Vulnerability Assessment method to 64 federally-managed species in the California Current Large Marine Ecosystem to assess their vulnerability to climate change, where vulnerability is a function of a species’ exposure to environmental change and its biological sensitivity to a set of environmental conditions, which includes components of its resiliency and adaptive capacity to respond to these new conditions. Results Overall, two-thirds of the species were judged to have Moderate or greater vulnerability to climate change, and only one species was anticipated to have a positive response. Species classified as Highly or Very Highly vulnerable share one or more characteristics including: 1) having complex life histories that utilize a wide range of freshwater and marine habitats; 2) having habitat specialization, particularly for areas that are likely to experience increased hypoxia; 3) having long lifespans and low population growth rates; and/or 4) being of high commercial value combined with impacts from non-climate stressors such as anthropogenic habitat degradation. Species with Low or Moderate vulnerability are either habitat generalists, occupy deep-water habitats or are highly mobile and likely to shift their ranges. Discussion As climate-related changes intensify, this work provides key information for both scientists and managers as they address the long-term sustainability of fisheries in the region. This information can inform near-term advice for prioritizing species-level data collection and research on climate impacts, help managers to determine when and where a precautionary approach might be warranted, in harvest or other management decisions, and help identify habitats or life history stages that might be especially effective to protect or restore.

Understanding Conformational Dynamics of Complex Lipid Mixtures Relevant to Biology - Ran Friedman; Syma Khalid; Camilo Aponte-Santamaría; Elena Arutyunova; Marlon Becker; Kevin J. Boyd; Mikkel Christensen; João T. S. Coimbra; Simona Concilio; Csaba Daday; Floris J. van Eerden; Pedro A. Fernandes; et al. (The Journal of Membrane Biology, 2018)

The mediating role of cortical thickness and gray matter volume on sleep slow-wave activity during adolescence - Aimée Goldstone; Adrian R. Willoughby; Massimiliano de Zambotti; Peter L. Franzen; Dongjin Kwon; Kilian M. Pohl; Adolf Pfefferbaum; Edith V. Sullivan; Eva M. Müller-Oehring; Devin E. Prouty; Brant P. Hasler; Duncan B. Clark; et al. (Brain Structure and Function, 2018)

Global low-frequency motions in protein allostery: CAP as a model system - Philip D. Townsend; Thomas L. Rodgers; Ehmke Pohl; Mark R. Wilson; Tom C. B. McLeish; Martin J. Cann (Biophysical Reviews, 2015)

Mineralogy, 57Fe Mössbauer spectra and magnetization of chalcolithic pottery - R. Keller; L. Masch; J. Pohl; E. Schmidbauer (Physics and Chemistry of Minerals, 2005)

Interrelations Between Thermal Conductivity and Other Physical Properties of Rocks: Experimental Data - Y. Popov; V. Tertychnyi; R. Romushkevich; D. Korobkov; J. Pohl (Pure and Applied Geophysics, 2003)

ITRF coordinates and plate velocities from repeated GPS campaigns in Antarctica - an analysis based on different individual solutions - R. Dietrich; R. Dach; G. Engelhardt; J. Ihde; W. Korth; H.-J. Kutterer; K. Lindner; M. Mayer; F. Menge; H. Miller; C. Müller; W. Niemeier; et al. (Journal of Geodesy, 2001)

Impaired direction and extent specification of aimed arm movements in humans with stroke-related brain damage - M. R. Velicki; C. J. Winstein; P. S. Pohl (Experimental Brain Research, 2000)

Diagnosis and Recommendation Integrated System (DRIS) zur Interpretation des Ernährungsstatus’ von Waldbäumen - H. N. Pohl; R. Vandré; Martin Kaupenjohann (European Journal of Forest Research, 1999)

Metamorphism and metallogeny in the Eastern Alps - W. Pohl; R. Belocky (Mineralium Deposita, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Klinik und Therapie einer erfolgreich behandelten, schweren Bromisovalerianylcarbamid-, Methaqualon- und Meprobamat-Vergiftung bei einem 12 Jahre alten Kind - F. Schindera; R. Gädeke; C. Ross; H. Höhmann; K. D. Pohl; M. Sauer; W. Bischoff (Archives of Toxicology, 1973)